In depth exploration of drivers of community health workers' performance in maternal and child health services: a multistakeholder perspective from rural Indian setting - Revadi Gouroumourty; Mukul Maheshwari; Anamika Prasad; Abhijit Pakhare; Ankur Joshi (BMC Primary Care)
Abstract Background Community health workers’ (CHWs') performance may be affected by several factors interplaying at the systemic level. There is a need to study those factors in the indigenous context to devise strategies for optimising the CHWs' performance. Hence, this study was conducted to understand the individual, health system and community level drivers of CHWs performance in Maternal and Child Health services and to decipher the interactions between CHWs and their stakeholders. Materials and methods A qualitative inquiry using pragmatic philosophy in a rural setting of Central India (Madhya Pradesh) was conducted. Firstly, relatively low and high performing CHWs were identified, and their stakeholders were selected through purposive sampling. A total of twenty in-depth interviews of CHWs, including their stakeholders, and two focused group discussions with nineteen participants were conducted. Manual thematic analysis was used to summarise the drivers of CHWs' performance. The 4 Cs subjective realistic model was created. The 4Cs of the model stand for the context of the shared responsibility; the clashes experienced by the CHWs (while working with their peers), complications and subsequent coherent measures from the stakeholders' perspective. Results The drivers of CHWs' performance were broadly constituted by three categories: contextual level, health system level and intrinsic contentment. The contextual factors include transport availability, community behaviour and heterogeneity in population. The determinants of health system were irregular incentives, scarcity of drugs, lack of peers’ support, patronage and benefaction. The intrinsic contentment was represented with sense of lack of recognition, family issues and natural causes. As per the realistic model, the clashes were related to network and transport availability, concurrent surveys, irregular incentives and peer support. These clashes led to the incompletion of tasks by CHWs which further resulted in supervisory challenges for the peers. The coherent measures suggested includes strengthening of supportive supervision and availability of regular incentives and transport. Conclusion The CHWs' performance was a derivation of inherent context, which was bidirectionally influenced by health systems concerns. The stakeholders’ interviews led to in depth understanding of the challenges faced by CHWs thereby adding validity to the qualitative inquiry.